A narrative review of rebound jumping and fast stretch-shortening cycle mechanics - Xu, J.; Turner, A.; Jordan, M. J.; Comyns, T. M.; Chavda, S.; Bishop, C. (Strength and Conditioning Journal, 2025)
Rebound jumping is one of the most commonly used movement patterns to assess and monitor fast stretch-shortening cycle (SSC) mechanics, a critical component for rapid movements like sprinting, jumping, and directional changes. This narrative review explores the mechanical and neuromuscular mechanics underlying fast SSC function and critically evaluates the strengths and weaknesses of commonly used testing protocols, including drop jumps and multiple rebound jump tests, along with commonly reported metrics from these tests. By integrating scientific evidence with practical applications, the aim of this review is to guide practitioners in selecting appropriate assessment tools and implementing evidence-based strategies to evaluate fast SSC performance in athletes.